A Primer in Biological Data Analysis and Visualization Using R - Hartvigsen, Gregg (Columbia University Press, 2021)
This text is an engaging, practical, and lab-oriented introduction to R for students in the life sciences. This second edition has been revised to be current with the versions of R software released since the book's original publication. It features updated terminology, sources, and examples throughout.